Pengembangan Multimedia Interaktif Permainan Bola Voli untuk Kelas XI SMA - Aji Saputra, Chandra Juniar; Widodo, Agus (Universitas Negeri Semarang, 2023)
The purpose of this study was to determine the feasibility, effectiveness and influence of the use of interactive multimedia volleyball on learning outcomes. The research design applied is R&D (Research and Development). The research was carried out at SMA Negeri 13 Semarang in class XI for the 2021/2022 academic year. The data collected in the form of: (1) learning outcomes (cognitive) preetest-posttest were analyzed with the percentage of classical completeness and N-gain test; (2) media validation test by experts (3) material validation test by experts; (4) student responses related to media; (5) results of teacher interviews. The results obtained are: (1) the results of classical completeness analysis on the posttest score of 100% of students reaching the KKM limit (2) the results of the N-gain test in class XI IPS 1 as many as 50% of students in the high category and 50% of students in the medium category ( 3) the results of the media validation test by experts obtained a score of 82.5 (very valid). (4) the results of the material validation test by experts obtained a score of 83.75 (very valid). (5) the results of the media assessment by students obtained that 70% of students gave very high ratings and 30% of students gave high ratings. The conclusion of this research is that interactive multimedia volleyball game is feasible and effective to use for class XI SMA.